Automatic Chocolate Vending Machine By Using Arduino Uno (International Journal of Innovative Research in Computer Science & Technology, 2024)
This paper proposes the design of Automatic  vending machine. The main objective of our project is to  launch new technology application in society. This is Arduino  based vending machine that sales different type of chocolates  from machine. This paper attempt to provide solution in coin  based vending machine which is not returned the amount of  money that is no any change from machine. The plan is to use  Radio frequency Identification along with Arduino. Once  RFID is to be read then User can select the product after card  is scanned and collects the product at output unit. There are  three parts; First part is scanning of RFID card which  provides cashless payment. The second is programming unit  which is implemented using arduino. The third part is display  information and deliver product at output. This paper  attempt to provide solution on coin based vending machine which is not returning the money.
Keywords: Arduino; RFID; interrogating; dialect